Physical Origin of Negative Differential Resistance in V3 O5 and Its Application as a Solid-State Oscillator - Das, Sujan Kumar (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2022 The Authors. Advanced Materials published by Wiley-VCH GmbH.